Sustained Actions in Combating Neglected Tropical Diseases during the COVID-19 Pandemic: Lessons Learned From the Leprosy Program in the Hyper-Endemic Area in Papua Province, Indonesia - Krismawati, Hana; Rochman, Mohhamad Fadjri; Oktavian, Antonius; Diana, Aly (Frontiers in Tropical Diseases, 2022)
In 2020 we witnessed the global pandemic of COVID-19. Papua, Indonesia announced the first case of COVID-19 on 7 March 2020, and reached 41,137 positive cases with a total of 1,183 fatality cases in August 2021. In the midst of the effort to handle COVID-19, this area of hyper-endemic tropical diseases, including leprosy, has also had to cope with these established problems. Some leprosy indicators have shown decreased performance. The new case detection rate (NCDR) per 100,000 population in Papua Province decreased from 45.36 in 2019 to 29.75 in December 2020. Grade 2 disability (G2D) proportion amongst the new cases increased from 9.0% in 2019 to 11.4% in 2020. There was a 27% decrease of the proportion of child leprosy, following the decrease of elementary school surveys from 6.1% in 2019 to only 1.0% in 2020. Although precautions should be taken, it should be done to minimalize impacts not only for the current pandemic, but also the existing neglected tropical diseases (NTDs). The central government should optimize their functions as a control system to maintain standard services and to monitor the local health authority. The current guidelines regarding implementation of NTD programs during the COVID-19 pandemic should be evaluated and revised, and followed by adequate explanation and proper training to accommodate better services. Emphasis on prevention and early detection should be considered as the main way forward to strengthen the health system.